2020
DOI: 10.1111/1462-2920.15113
|View full text |Cite
|
Sign up to set email alerts
|

DNAtandem repeats contribute to the genetic diversity of Brevibacterium aurantiacum phages

Abstract: Summary This report presents the characterization of the first virulent phages infecting Brevibacterium aurantiacum, a bacterial species used during the manufacture of surface‐ripened cheeses. These phages were also responsible for flavour and colour defects in surface‐ripened cheeses. Sixteen phages (out of 62 isolates) were selected for genome sequencing and comparative analyses. These cos‐type phages with a long non‐contractile tail currently belong to the Siphoviridae family (Caudovirales order). Their gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 85 publications
2
17
0
Order By: Relevance
“…Remarkably, a domain prediction using the online tool InterPro [74] revealed that Clg55 also contains a galactose-binding superfamily domain (data not shown). In a recent study focusing on Brevibacterium aurantiacum phages, De Melo and colleagues detected tandem repeat areas in 85% of all phage genomes available in public databases [75].…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, a domain prediction using the online tool InterPro [74] revealed that Clg55 also contains a galactose-binding superfamily domain (data not shown). In a recent study focusing on Brevibacterium aurantiacum phages, De Melo and colleagues detected tandem repeat areas in 85% of all phage genomes available in public databases [75].…”
Section: Discussionmentioning
confidence: 99%
“…Erkus et al [85] demonstrated that phage-sensitive strains are replaced by phage-insensitive strains of the same lineage, allowing for continued fermentation when using the complex Gouda cheese starter culture Ur. The composition of the original starter culture was dissected using culture-dependent and independent methods, allowing for community monitoring using genetic lineage-specific qPCR.…”
Section: Role Of Virulent Phages In Modulating Microbial Composition ...mentioning
confidence: 99%
“…The culture was able to maintain the relative composition of the different lineages, despite phage (originating from the original starter culture) pressure on individual strains. This was determined to be due to heterogeneity of the culture and, more specifically, variations in phage sensitivity of strains within and between lineages [85] .…”
Section: Role Of Virulent Phages In Modulating Microbial Composition ...mentioning
confidence: 99%
“…Brevibacterium aurantiacum phages isolated from cheese [18]**. They were classified into 7 distinct genomic groups based on the number of DNA tandem repeats (TRs) in each genome.…”
Section: Culture-dependent Approachesmentioning
confidence: 99%
“…The hosts are usually members of the dominant species present in the corresponding food, such as Leuconostoc mesenteroides in Sauerkraut [21] or Oenococcus oeni in Wine [22]. For the particular case of cheese, where an abundant literature regarding phages infecting Lactic Acid Bacteria (LAB) starter cultures is available, as reviewed previously [23,24], only a few studies described the isolation of phages infecting other important bacteria such as Propionibacterium freudenreichii [15], the bacteria responsible for the production of holes in Emmental-type cheese, Brevibacterium aurantiacum [18], a surface ripening culture used in many cheese varieties and Enterococcus faecalis [25,26]*. However, in the perspective of understanding the bacteriophage ecology in fermented foods, single phage isolation suffer from the major limitation of the culture-dependent approach that is the need of a susceptible host.…”
Section: Culture-dependent Approachesmentioning
confidence: 99%